Diastereoselective Palladium-Catalyzed [4+1] Cycloadditions of 4-Vinyl-1,4-dihydro-2H-3,1-benzoxazin-2-ones with In Situ Formed Carbenes - Ma, Yan-Hua; Meng, Fan-Xiao; Wang, Ruo-Nan; Fan, Ya-Xin; Su, Qing-Qiang; Du, Ji-Yuan (Synthesis, 2021)
Herein, we present a palladium-catalyzed tandem [4+1] cycloaddition of 4-vinyl-1,4-dihydro-2H-3,1-benzoxazin-2-ones with N-tosylhydrazones. The reaction is accomplished by merging the in situ generated aza-ortho-quinone methides (aza-o-QMs) with nucleophilic carbenes. This method enables the construction of diverse indolines with broad functional group compatibility in good yields with high levels of diastereoselectivity under mild conditions.
Keywords: aza-o-quinone methides; dihydroindole; [4+1] cycloadditions; Pd(0)-catalyzed; benzoxazinones; carbenes